Suburbanization and Mass Culture in North America - Belisle, Donica (Labour / Le Travail, 2006)
The article reviews and comments on several books including "Creeping Conformity: How Canada Became Suburban, 1900-1960," by Richard Harris, "Manufacturing Suburbs: Building Work and Home on the Metropolitan Fringe," by Robert Lewis and "A Great Duty: Canadian Responses to Modern Life and Mass Culture, 1939-1967," by Len Kuffert.
Keywords: BOOKS – Reviews; CREEPING Conformity: How Canada Became Suburban 1900-1960 (Book); GREAT Duty: Canadian Responses to Modern Life & Mass Culture 1939-1967; A (Book); HARRIS; Richard; KUFFERT; Len; LEWIS; Robert; MANUFACTURING Suburbs: Building Work & Home on the Metropolitan Fringe (Book); Nonfiction